STTBoost: A Hybrid Road Traffic Congestion Prediction Model Using Transformer and XGBoost - Deepti Soni (International Journal of Intelligent Systems and Applications in Engineering, 2023)
Accurate traffic congestion prediction is crucial for effectively managing urban transportation systems. Traditional models often focus on either speed or density factors independently, which limits their ability to capture the complex dynamics of real-world traffic conditions. This paper proposes a hybrid approach that integrates both speed and density factors to enhance the realism and accuracy of congestion prediction. The standard TCI is modified to combine density with speed, and a modified Traffic Congestion Index (M_TCI) is proposed. A new hybrid model called STTBoost (Spatio-temporal Transformer Boost) is also proposed, which uses the strengths of Transformer networks and XGBoost to predict traffic congestion. The Transformer model captures spatial-temporal dependencies, whereas XGBoost excels at handling nonlinear patterns. The integration of these two models is used for robust predictions, especially when contextual features, such as road characteristics, road incidents, and temporal patterns, are included. The proposed hybrid model, tested on real-world datasets, demonstrates significant improvements in prediction accuracy, offering a powerful tool for modern traffic management systems. This approach addresses the shortcomings of existing models by providing a more comprehensive and realistic method for congestion forecasting.